2000
DOI: 10.1182/blood.v96.1.80
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind trial of filgrastim (granulocyte colony-stimulating factor) versus placebo following allogeneic blood stem cell transplantation

Abstract: Blood stem cell transplantation (BSCT) results in rapid hematopoietic recovery in both the allogeneic and autologous transplant settings. Because of the large numbers of progenitor cells in mobilized blood, the administration of growth factors after transplantation may not provide further acceleration of hematopoietic recovery. A randomized, double-blind, placebo-controlled study was performed to determine the effects of filgrastim (granulocyte colony-stimulating factor; G-CSF) administration on hematopoietic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…reported a significantly faster neutrophil recovery [8]. Furthermore, in a randomized double‐blind trial of G‐CSF 10 µg/kg/day (N = 26) vs. placebo (N = 24) administered after allogeneic BMT, G‐CSF also resulted in significantly more rapid neutrophil recovery (11 vs. 15 days for placebo, P = 0.008) [4]. More recently, a retrospective database analysis by Khoury et al.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…reported a significantly faster neutrophil recovery [8]. Furthermore, in a randomized double‐blind trial of G‐CSF 10 µg/kg/day (N = 26) vs. placebo (N = 24) administered after allogeneic BMT, G‐CSF also resulted in significantly more rapid neutrophil recovery (11 vs. 15 days for placebo, P = 0.008) [4]. More recently, a retrospective database analysis by Khoury et al.…”
Section: Discussionmentioning
confidence: 98%
“…Additional risk factors for mortality include infections that arise as a result of neutropenia and prolonged immune deficiency. Recombinant human granulocyte colony‐stimulating factor (G‐CSF) or granulocyte macrophage colony‐stimulating factor (GM‐CSF) may be administered after allogeneic transplantation of either bone marrow or peripheral blood stem cells to enhance engraftment [2–7]. Some authors report that patients receiving growth factors post allogeneic stem cell transplant experience faster neutrophil recovery and no adverse effects in terms of graft versus host disease (GvHD) [4,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daily G-CSFs, such as filgrastim or lenograstim, should be administered daily until the expected neutrophil nadir is passed and the neutrophil count has recovered to the normal range, which usually requires up to 2 weeks of treatment. In clinical trials where daily G-CSFs were continued until either the neutrophil count reached Ն10 ¥ 10 9 /L or for up to 14 days, whichever occurred first, the mean duration of G-CSF prophylaxis was up to 10-11 days (Dale et al 1993;Muhonen et al 1996;Bishop et al 2000;Holmes et al 2002b;Green et al 2003;Siena et al 2003). However, several observational studies have reported that in most patients treated in the clinical practice, duration of prophylaxis with daily G-CSFs is less than 7 days, and that a short duration of daily G-CSF treatment is associated with worse neutropenia-related clinical outcomes (Weycker et al 2006;Morrison et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In allogeneic HSCT, the use of GCSF leads to an improvement in neutrophil engraftment of 1-4 days in comparison with observation (13)(14)(15)(16)(17)(18)(19)(20) or placebo (9,21). This is borne out in both PBSCT and BMT studies, with only one retrospective BMT study not supporting this Abbreviations: ASCO, American Society of Clinical Oncology; BMT, bone marrow transplantation; GCSF, granulocyte colony stimulating factor; GMCSF, granulocyte macrophage colony stimulating factor; GvHD, graftversus-host disease; HSCT, hematopoietic stem cell transplant; IV, intravenous; PBSCT, peripheral blood stem cell transplant; SC, subcutaneous; TPN, total parenteral nutrition; TRM, transplant-related mortality.…”
mentioning
confidence: 99%